Protestantism in contemporary china - Hunter, Alan; Chan, Kim-Kwong (Cambridge ; New York Cambridge University Press, 1993)
This study investigates the historical and political conditions which have contributed to the current state of the Protestant community in China, and the kinds of spirituality and religious life that it has evolved. The authors draw on extensive fieldwo
Keywords: China -- Church history. Protestants -- China. China -- Religion